2017
DOI: 10.17738/ajes.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate cementation in Upper Eocene clastic reservoir rocks from the North Alpine Foreland Basin (Austria)

Abstract: A strong relationship between carbonate precipitation and microbial gas generation is evident for the Upper Eocene reservoir rocks of the North Alpine Foreland Basin. To achieve a better understanding of this relationship, 40 samples of limnic to shallow marine, gas-, oil-and water-bearing sandstones were studied to determine mineralogy and diagenetic history. The specific mineral parageneses were used to reconstruct changes in the hydrogeochemical conditions over time. Thus, authigenic mineral phases within r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, only a minor amount of hydrocarbons migrated from underlying shales after thermal maturation. Grundtner et al (2017) reported similar isotopic values in calcite cement of Upper Eocene sandstone from the North Alpine Foreland Basin (Austria) and concluded that cementation occurred during advanced stage of sulphate reduction. The possible source of Mg in this calcite can be the ankerite which was replaced by these calcite phases.…”
Section: Calcite -Core Sectionmentioning
confidence: 74%
“…Accordingly, only a minor amount of hydrocarbons migrated from underlying shales after thermal maturation. Grundtner et al (2017) reported similar isotopic values in calcite cement of Upper Eocene sandstone from the North Alpine Foreland Basin (Austria) and concluded that cementation occurred during advanced stage of sulphate reduction. The possible source of Mg in this calcite can be the ankerite which was replaced by these calcite phases.…”
Section: Calcite -Core Sectionmentioning
confidence: 74%
“…Shallow-marine sandstones of the Ampfing Formation are laterally more continuous than the channel sandstones of the Voitsdorf Formation and the Cerithian Beds and have a net thickness of 10 m. Most sandstones show moderate sorting and are classified as lithic arkoses, but litharenites, subarkoses and sublitharenites are also observed in the northern part of the North Alpine Foreland Basin (Fig. 5) (Grundtner et al, 2017). Rare glauconite and the presence of foraminifera support a marine depositional environment.…”
Section: Eocene (Voitsdorf Formation Cerithian Beds Ampfing Formation)mentioning
confidence: 96%
“…Whereas carbonate cement is typically rare in non-marine to brackish sandstones, the amount of carbonate cement in sandstones of the marine Ampfing Formation often exceeds >5 vol%. Early diagenetic carbonate precipitation, promoted by alkaline conditions, prevented further compaction but the carbonate was was later partly dissolved (Grundtner et al, 2017). The isotopic composition of the carbonate cement indicates the non-marine formation of carbonate minerals in the Voitsdorf Formation and the Cerithian Beds, and a meteoric flush in the laterally-continuous Ampfing Formation.…”
Section: Eocene (Voitsdorf Formation Cerithian Beds Ampfing Formation)mentioning
confidence: 96%
See 2 more Smart Citations